Communicating Science and Technology in Society: Issues of Public Accountability and Engagement - Delicado, Ana (2021)
​This volume addresses the engagement between science and society from multiple viewpoints. At a time when trust in experts is being questioned, misinformation is rife and scientific and technological development show growing social impact, the volume examines the challenges in involving the public in scientific debates and decisions. It takes into account societal needs and concerns in research, and analyses the interface between the roles of institutions and individuals. From environmental challenges to science communication, participatory technological design to animal experimentation, and transdisciplinarity to norms and values in science, the volume brings together research on areas in which scientists and citizens interact, across diverse, often understudied, socio-cultural contexts in Europe. It encompasses the natural sciences, engineering and the social sciences, and the chapters follow diverse theoretical frameworks and methodologies, including both quantitative and qualitative approaches. This volume contributes not just to scholarly knowledge on the topic of science and society relations, but also provides useful information for students, policy makers, journalists, and STEM (science, technology, engineering and mathematics) researchers keen on engaging with their publics and conducting responsible research and innovation.